1988
DOI: 10.1007/bf01310835
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of foxes against rabies with a vaccinia recombinant virus expressing the rabies glycoprotein

Abstract: Foxes were vaccinated orally (by bait), gastrically (by stomach tube) and by scarification with a vaccinia recombinant virus expressing the rabies glycoprotein. Neutralizing antibodies against rabies virus were detected at two weeks postvaccination in 8/8 foxes in the bait-fed group, in 3/6 foxes inoculated by stomach tube and in 2/2 of the scarified foxes. After challenge at three months postvaccination with street rabies virus, all foxes that had developed antibodies were protected. The high rate of seroconv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
1
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 9 publications
1
14
1
1
Order By: Relevance
“…The vaccinia-vectored rabies vaccine is safe in this species but has been suggested to be ineffective (Charlton et al, 1992). This statement is in contrast to a study in which efficacy was demonstrated in skunks given relatively high titers (10 9.0 pfu/ dose) of virus by multiple routes (Tolson et al, 1987). Our study was conducted to determine if a commercial serial of the recombinant vaccinia virus, when given by direct instillation into the oral cavity, could protect caged skunks against a virulent rabies challenge.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…The vaccinia-vectored rabies vaccine is safe in this species but has been suggested to be ineffective (Charlton et al, 1992). This statement is in contrast to a study in which efficacy was demonstrated in skunks given relatively high titers (10 9.0 pfu/ dose) of virus by multiple routes (Tolson et al, 1987). Our study was conducted to determine if a commercial serial of the recombinant vaccinia virus, when given by direct instillation into the oral cavity, could protect caged skunks against a virulent rabies challenge.…”
contrasting
confidence: 52%
“…Absorbent paper was not placed in cages during the vaccine trial since doing so often interfered with bait acceptance. Tolson et al (1987) previously demonstrated oral vaccine efficacy in skunks immunized with 5.0 ml of vaccinia-vectored recombinant rabies vaccine given at 109 pfu/dose. Tolson's success, on an experimental scale, was due to a larger vaccine volume held within a polyurethane sponge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this strain the cDNA corresponding to the glycoprotein of the ERA strain of rabies virus has been incorporated under the control of the 7.5K promoter into the thymidine kinase (TK) gene of VV. This virus (VVTGgRAB) was demonstrated to be effective for the oral immunization of foxes, raccoons and skunks, eliciting high titres of rabies virus-neutralizing antibodies and conferring long-term protection against rabies (Blancou et al, 1986;Rupprecht et al, 1986Rupprecht et al, , 1988Tolson et al, 1987Tolson et al, , 1988Brochier et al, 1988b). Oral administration of VVTGgRAB was shown to be perfectly safe for several domestic Soria Baltazar et al, 1987), laboratory (Wiktor et al, 1988) and wildlife species Rupprecht et al, 1986Rupprecht et al, , 1988Tolson et al, 1987Tolson et al, , 1988.…”
Section: Introductionmentioning
confidence: 99%
“…This virus (VVTGgRAB) was demonstrated to be effective for the oral immunization of foxes, raccoons and skunks, eliciting high titres of rabies virus-neutralizing antibodies and conferring long-term protection against rabies (Blancou et al, 1986;Rupprecht et al, 1986Rupprecht et al, , 1988Tolson et al, 1987Tolson et al, , 1988Brochier et al, 1988b). Oral administration of VVTGgRAB was shown to be perfectly safe for several domestic Soria Baltazar et al, 1987), laboratory (Wiktor et al, 1988) and wildlife species Rupprecht et al, 1986Rupprecht et al, , 1988Tolson et al, 1987Tolson et al, , 1988. Taking into account all the available experimental data 0000-9071 © 1990 GM concerning the efficacy and safety of this recombinant, a preliminary restricted field trial of fox vaccination against rabies was carried out in 1987 in Belgium (Pastoret et al, 1988).…”
Section: Introductionmentioning
confidence: 99%